MANAGEMEN NYERI UNTUK MENGATASI MASALAH NYERI AKUT POST OPERASI PADA PENDERITA BENIGNA PROSTAT HYPERPLASIA - Farah Nuri Azizah ,; Amin Susanto ,; Asmat Burhan, (JURNAL PENGABDIAN MANDIRI, 2022)
Benign Postat Hyperlasia (BPH) is the use of the prostate gland that is benign only in men, usually in middle or old age. The incidence of benign prostatic hyperplasia (BPH) in Indonesia has placed BPH as the number two cause of urinary tract stones. This paper uses a descriptive case study in the form of a nursing care case study which includes assessment, nursing diagnosis, nursing plan, nursing implementation, and nursing evaluation. Data collection techniques were carried out by interview, observation, and documentation. The results of the case study Mr. A with postoperative TURP obtained one nursing diagnosis, namely acute pain. After nursing actions, the patient shows a change in condition for the better, namely the client can adapt to postoperative pain. conclusion of the case study on Mr. A with acute postoperative pain TURP is a problem resolved according to the goals and expected outcome criteria.